Unveiling Functions and Patterns of Intra-Sentential Code-Switching in the Video Podcast 'Culture Shock Kuliah di Inggris' on YouTube Channel - Suwastini, Ni Komang Arie; Anggara, I Putu Dipa; Mahendrayana, Gede; Mahayanti, Ni Wayan Surya (TARBIYA: Journal of Education in Muslim Society, 2024)
AbstractThe research delves into code-switching among Indonesian speakers in the UK, covering the syntactic and functional reasons why they use code-switching in intra-sentential contexts by applying Poplack's theory in syntactic and Hoffmann's theory in functional. Data collection includes repeated video watching, taking notes, and categorising code-switching used in the video podcast. Those steps require repeated execution to ensure accurate and comprehensive data collection and analysis. After categorising and identifying patterns of code-switching, it is followed by interpreting the findings and making connections to Poplacks and Hoffmans’ theories which led to the conclusion-drawing. The analysis presents nine states of intra-sentential switching parts of speech and seven categories of code-switching functions. Of 134 instances of code-switching, 104 were intra-sentential, with ICs being the most common (32%). Speakers primarily used code-switching to discuss specific topics, accounting for 37.67% of all instances. The results indicate that speakers would rather negotiate higher units, such as clauses, because the language feature is part of their regular use of English in the UK. This study demonstrates how code-switching helps with communication and identity formation for bilingual speakers. In relevance for language education, code-switching, as a pedagogical tool, can enhance comprehension and participation in language education programs, particularly in more complexly multilingual classrooms. Future research should also examine code-switching in various cultural contexts and use interdisciplinary methodologies to fully fund this linguistic phenomenon. AbstrakPenelitian ini menyelidiki peralihan kode di antara penutur bahasa Indonesia di Inggris, yang mencakup alasan sintaksis dan fungsional mengapa mereka menggunakan peralihan kode dalam konteks intra-kalimat dengan menerapkan teori Poplack dalam sintaksis dan teori Hoffmann dalam fungsional. Pengumpulan data meliputi menonton video berulang kali, membuat catatan, dan mengkategorikan peralihan kode yang digunakan dalam podcast video. Langkah-langkah tersebut memerlukan pelaksanaan berulang untuk memastikan pengumpulan dan analisis data yang akurat dan komprehensif. Setelah mengkategorikan dan mengidentifikasi pola peralihan kode, analisis dilanjutkan dengan menafsirkan temuan dan menghubungkan dengan teori Poplack dan Hoffman yang mengarah pada penarikan kesimpulan. Analisis ini menyajikan sembilan keadaan bagian-bagian pidato peralihan intra-kalimat dan tujuh kategori fungsi peralihan kode. Dari 134 contoh alih kode, 104 di antaranya adalah intra-kalimat, dengan IC menjadi yang paling umum (32%). Penutur terutama menggunakan alih kode untuk membahas topik-topik tertentu, yang mencakup 37,67% dari semua contoh. Hasilnya menunjukkan bahwa penutur lebih suka menegosiasikan unit-unit yang lebih tinggi, seperti klausa, karena fitur bahasa adalah bagian dari penggunaan bahasa Inggris mereka secara teratur di Inggris. Studi ini menunjukkan bagaimana alih kode membantu komunikasi dan pembentukan identitas bagi penutur bilingual. Dalam relevansi untuk Pendidikan Bahasa, alih kode, sebagai alat pedagogis, dapat meningkatkan pemahaman dan partisipasi dalam program pendidikan bahasa, khususnya di kelas-kelas multibahasa yang lebih kompleks. Penelitian di masa mendatang juga harus memeriksa alih kode dalam berbagai konteks budaya dan menggunakan metodologi interdisipliner untuk sepenuhnya mendanai fenomena linguistik ini. How to Cite: Suwastini, N. K. A., Anggara, I. P. D., Mahendrayana, G., & Mahayanti, N. W. S. (2024). Unveiling Functions and Patterns of Intra-Sentential Code-Switching in the Video Podcast 'Culture Shock Kuliah di Inggris' on YouTube Channel. TARBIYA: Journal of Education in Muslim Society, 11(2), 135-158. doi:10.15408/tjems.v11i2.39295.